Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-Cov-2) Infection in Household Contacts and Related Factors During the First and Second Waves of the Covid-19 Pandemic in Chile: A Longitudinal Cohort Study - Sandino-Garcia, A (European Publishing, 2023)
Background: Households are the high-risk setting for SARS-CoV-2 transmission, especially for close and prolonged person-to-person contact. However, the role of household structural and clinical factors, especially angiotensin-converting enzyme 2 (ACE2), is scarce studied. We analyzed the household SARS-CoV-2 infection during the first and second waves of the COVID-19 outbreak and associated factors in household contacts. Methods: We conducted a prospective cohort study of 109 household clusters with a 60-day follow-up (109 index cases and 248 household contacts) in a selected population in Santiago de Chile. Home interviewers measured: compliance with non-pharmaceutical interventions, household structures, symptoms questionnaire; comorbidities and periodontal condition self-report; and saliva samples and nasopharyngeal swabs for ACE2 and SARS-CoV-2 viral load determination. The secondary attack rate (SAR) of SARS-CoV-2 risk factors was assessed using Poisson random-mixed models. Incidence Rate Ratios (IRR) and p-values are reported. Results: The baseline SAR in household contacts was 0.478 (within household variations of 0.03) and 0.488 at the end of the follow-up. Of infected households, 13.6% of contacts were asymptomatic at baseline 23.7% and 12.7% at 7-day and 14-day follow-up, respectively. Infected household contacts were younger (35.9 y vs. 41.1 y, p=0.02), less hypertensive (9.3% vs. 18.5%, p=0.03), and had lower levels of ACE2 (0.04 ng/dl vs. 0.07 ng/dl, p=0.02) than those uninfected. Factors associated with household transmission were a greater number of adult inhabitants (IRR 0.77. p<0.01) and a greater number of rooms (IRR 0.8, p=.003). Conclusions: In our study, during a COVID-19 when index cases were enrolled, more than 48% of their household contacts were already infected. The composition and structure of the home play an essential role in preventing household SARS-CoV-2 transmission. The ACE2 levels may play an important role in household contacts, but further studies are needed. © (2023), (European Publishing). All Rights Reserved.